2011
DOI: 10.1186/1746-1596-6-4
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoepithelioma-like carcinoma of the vulva, an underrecognized entity? Case report with a single inguinal micrometastasis detected by sentinel node technique

Abstract: This report describes an unusual EBV-negative lymphoepithelioma-like carcinoma of the vulva in a 73-year-old patient. The lesion was localised at the right minor labium and was resected by partial vulvectomy. A synchronous sentinel lymph node biopsy revealed a single micrometastasis in the right inguinal region, which prompted local radiotherapy. Follow-up nine months later showed only slight vulvar atrophy, without signs of local recurrence or distant metastases.Although lymphoepithelioma-like carcinomas of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…PLEC is analogus and exhibits identical histopathological characteristics as non-keratinizing, undifferentiated nasopharyngeal carcinomas (NPC) 3 . However PLEC arises in organs other than nasopharynx, such as larynx 4 , tonsils 5 , lung 6 , thymus 7 , stomach and duodenum 8 , breast 9 , renal pelvis and urinary bladder 10 , uterine cervix 11 , endometrium 12 , ovary 13 , vulva and vagina 14 .…”
Section: Primarymentioning
confidence: 99%
“…PLEC is analogus and exhibits identical histopathological characteristics as non-keratinizing, undifferentiated nasopharyngeal carcinomas (NPC) 3 . However PLEC arises in organs other than nasopharynx, such as larynx 4 , tonsils 5 , lung 6 , thymus 7 , stomach and duodenum 8 , breast 9 , renal pelvis and urinary bladder 10 , uterine cervix 11 , endometrium 12 , ovary 13 , vulva and vagina 14 .…”
Section: Primarymentioning
confidence: 99%
“…In the genital tract, this pathological entity is very rare, mainly described in the cervix, where it could be associated with Human Papillomavirus (HPV) infection [47]. Exceptionally, these tumors have been also encountered in the rest of genital tract including vulva, vagina, ovary, and endometrium [811]. In the endometrium, to the best of our knowledge, only 5 cases of lymphoepithelioma-like carcinoma have been reported [1216].…”
Section: Introductionmentioning
confidence: 99%
“…The association with EBV infection in LELC is different in various locations and in different geographic regions. EBV positivity has been described in tumours of lung, stomach, thymus, and salivary gland [2,3,4,5], but it has not been demonstrated in cases of LELC occurring in the urinary bladder, renal pelvis, breast, and in the female genital tract [6,7,8,9,10]. It has been suggested that EBV positivity is related to a direct organ exposure to the external environment, and EBV negativity is more common in internal organs [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, in LELC of uterine cervix the association with EBV has been observed only in a few Asian patients, but not in western countries [12,13]. In the female genital tract LELC mostly occurs in the cervix, where it is regarded as a variant of squamous cell carcinoma, but cases involving the vulva, vagina, endometrium, and ovary have also been reported [9,10,12,13,14,15,16,17,18,19]. To the best of our knowledge, only six cases of LELC arising in the endometrium have been reported to date; however, none of these was accompanied by a molecular genetic analysis, with the exception of molecular testing for microsatellite instability (MSI) in one of the cases [14,15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%